Free Fatty Acid-induced β-Cell Defects Are Dependent on Uncoupling Protein 2 Expression - Jamie W. Joseph; Vasilij Koshkin; Monique C. Saleh; William I. Sivitz; Chenyu Zhang; Bradford B. Lowell; Catherine B. Chan; Michael B. Wheeler (2004)
Chronic exposure to elevated free fatty acids (lipotoxicity) induces uncoupling protein (UCP2) in the pancreatic β-cell, and therefore a causal link between UCP2 and β-cell defects associated with obesity may exist. Recently, we showed that lipid treatment in vivo and in vitro in UCP2(–/–) mice/islets does not result in any loss in β-cell glucose sensitivity. We have now assessed the mechanism of maintained β-cell function in UCP2(–/–) mice by exposing islets to 0.4 mm palmitate for 48 h. Palmitate treatment increased triglyceride concentrations in wild type (WT) but not UCP2(–/–) islets because of higher palmitate oxidation rates in the UCP2(–/–) islets. Dispersed β-cells from the palmitate-exposed WT islets had reduced glucose-stimulated hyperpolarization of the mitochondrial membrane potential compared with both control WT and palmitate-exposed UCP2(–/–) β-cells. The glucose-stimulated increases in the ATP/ADP ratio and cytosolic Ca2+ are attenuated in palmitate-treated WT but not UCP2(–/–) β-cells. Exposure to palmitate reduced glucose-stimulated insulin secretion (GSIS) in WT islets, whereas UCP2(–/–) islets had enhanced GSIS. Overexpression of recombinant UCP2 but not enhanced green fluorescent protein in β-cells resulted in a loss of glucose-stimulated hyperpolarization of the mitochondrial membrane potential and GSIS similar to that seen in WT islets exposed to palmitate. Reactive oxygen species (ROS) are known to increase the activity of UCP2. We showed that ROS levels were elevated in control UCP2(–/–) islets as compared with WT and UCP2(–/–) islets overexpressing UCP2 and that palmitate increased ROS in WT and UCP2(–/–) islets overexpressing UCP2 but not in UCP2(–/–) islets. Thus, UCP2(–/–) islets resisted the toxic effects of palmitate by maintaining glucose-dependent metabolism-secretion coupling. We propose that higher free fatty acid oxidation rates prevent accumulation of triglyceride in UCP2(–/–) islets, such accumulation being a phenomenon associated with lipotoxicity. Chronic exposure to elevated free fatty acids (lipotoxicity) induces uncoupling protein (UCP2) in the pancreatic β-cell, and therefore a causal link between UCP2 and β-cell defects associated with obesity may exist. Recently, we showed that lipid treatment in vivo and in vitro in UCP2(–/–) mice/islets does not result in any loss in β-cell glucose sensitivity. We have now assessed the mechanism of maintained β-cell function in UCP2(–/–) mice by exposing islets to 0.4 mm palmitate for 48 h. Palmitate treatment increased triglyceride concentrations in wild type (WT) but not UCP2(–/–) islets because of higher palmitate oxidation rates in the UCP2(–/–) islets. Dispersed β-cells from the palmitate-exposed WT islets had reduced glucose-stimulated hyperpolarization of the mitochondrial membrane potential compared with both control WT and palmitate-exposed UCP2(–/–) β-cells. The glucose-stimulated increases in the ATP/ADP ratio and cytosolic Ca2+ are attenuated in palmitate-treated WT but not UCP2(–/–) β-cells. Exposure to palmitate reduced glucose-stimulated insulin secretion (GSIS) in WT islets, whereas UCP2(–/–) islets had enhanced GSIS. Overexpression of recombinant UCP2 but not enhanced green fluorescent protein in β-cells resulted in a loss of glucose-stimulated hyperpolarization of the mitochondrial membrane potential and GSIS similar to that seen in WT islets exposed to palmitate. Reactive oxygen species (ROS) are known to increase the activity of UCP2. We showed that ROS levels were elevated in control UCP2(–/–) islets as compared with WT and UCP2(–/–) islets overexpressing UCP2 and that palmitate increased ROS in WT and UCP2(–/–) islets overexpressing UCP2 but not in UCP2(–/–) islets. Thus, UCP2(–/–) islets resisted the toxic effects of palmitate by maintaining glucose-dependent metabolism-secretion coupling. We propose that higher free fatty acid oxidation rates prevent accumulation of triglyceride in UCP2(–/–) islets, such accumulation being a phenomenon associated with lipotoxicity. In the pancreatic β-cell, glucose is metabolized by glycolysis producing pyruvate and nicotinamide adenine dinucleotide (NADH), both of which are transported into the mitochondria where pyruvate is metabolized by the tricarboxylic acid cycle to produce NADH and flavin adenine dinucleotide (FADH2). Both cytosolic and mitochondrial sources of NADH along with mitochondrial FADH2 stimulate the electron transport chain (complexes I–IV) to pump H+ ions out of the mitochondrial matrix, thereby hyperpolarizing the inner mitochondrial membrane and generating the proton-motive force used to generate ATP by ATP synthase (1Erecinska M. Bryla J. Michalik M. Meglasson M.D. Nelson D. Biochim. Biophys. Acta. 1992; 1101: 273-295Crossref PubMed Scopus (120) Google Scholar). Mitochondrial ATP production from glucose is the key modulator of glucose-stimulated insulin secretion (GSIS), 1The abbreviations used are: GSIS, glucose-stimulated insulin secretion; UCP, uncoupling protein; WT, wild type; HFD, high fat diet; FFA, free fatty acids; ROS, reactive oxygen species; Δψm, mitochondrial membrane potential; FCCP, carbonyl cyanide p-(trifluoromethoxy) phenylhydrazone; KRBH, Krebs-Ringer-bicarbonate-HEPES; TG, triglycerides; DCF, 2′,7′-dichlorodihydrofluorescein diacetate; GAPDH, glyceraldehyde-3-phosphate dehydrogenase; Rh123, rhodamine 123; MnTBAP, Mn(III) tetrakis-(4-benzoic acid) porphyrin; EGFP, enhanced green fluorescent protein; EYFP, enhanced yellow fluorescent protein. and mitochondrial oxidative metabolism has been estimated to produce 98% of β-cell ATP (1Erecinska M. Bryla J. Michalik M. Meglasson M.D. Nelson D. Biochim. Biophys. Acta. 1992; 1101: 273-295Crossref PubMed Scopus (120) Google Scholar). The members of the uncoupling protein (UCP) family are involved in regulating cellular ATP production and are localized to the inner mitochondrial membrane (2Boss O. Hagen T. Lowell B.B. Diabetes. 2000; 49: 143-156Crossref PubMed Scopus (392) Google Scholar). Uncoupling protein-1, -2, and -3 share a high degree of homology and are expressed in a tissue-specific manner (3Klingenberg M. Huang S.G. Biochim. Biophys. Acta. 1999; 1415: 271-296Crossref PubMed Scopus (316) Google Scholar). Data from several laboratories support a role for UCPs as "typical" uncouplers (4Echtay K.S. Winkler E. Klingenberg M. Nature. 2000; 408: 609-613Crossref PubMed Scopus (296) Google Scholar, 5Echtay K.S. Roussel D. St Pierre J. Jekabsons M.B. Cadenas S. Stuart J.A. Harper J.A. Roebuck S.J. Morrison A. Pickering S. Clapham J.C. Brand M.D. Nature. 2002; 415: 96-99Crossref PubMed Scopus (1150) Google Scholar) that modulate the efficiency of ATP production (3Klingenberg M. Huang S.G. Biochim. Biophys. Acta. 1999; 1415: 271-296Crossref PubMed Scopus (316) Google Scholar) by catalyzing the translocation of protons across the mitochondrial membrane to reduce the proton-motive force (4Echtay K.S. Winkler E. Klingenberg M. Nature. 2000; 408: 609-613Crossref PubMed Scopus (296) Google Scholar, 5Echtay K.S. Roussel D. St Pierre J. Jekabsons M.B. Cadenas S. Stuart J.A. Harper J.A. Roebuck S.J. Morrison A. Pickering S. Clapham J.C. Brand M.D. Nature. 2002; 415: 96-99Crossref PubMed Scopus (1150) Google Scholar). Moreover, UCP2 mediates proton leak within the normal environment of intact cells (6Krauss S. Zhang C.Y. Lowell B.B. Proc. Natl. Acad. Sci. U. S. A. 2002; 99: 118-122Crossref PubMed Scopus (154) Google Scholar). UCP2 is the only known uncoupling protein expressed in pancreatic β-cells (7Chan C.B. MacDonald P.E. Saleh M.C. Johns D.C. Marban E. Wheeler M.B. Diabetes. 1999; 48: 1482-1486Crossref PubMed Scopus (229) Google Scholar). The human UCP2 promoter polymorphism –866 G/A is associated with a greater risk of obesity in Caucasians (8Esterbauer H. Schneitler C. Oberkofler H. Ebenbichler C. Paulweber B. Sandhofer F. Ladurner G. Hell E. Strosberg A.D. Patsch J.R. Krempler F. Patsch W. Nat. Genet. 2001; 28: 178-183Crossref PubMed Scopus (333) Google Scholar). Type 2 diabetic patients homozygous for the –866A allele polymorphism require a higher frequency of insulin treatments and have significantly lower glucose-induced insulin secretion (9Sasahara M. Nishi M. Kawashima H. Ueda K. Sakagashira S. Furuta H. Matsumoto E. Hanabusa T. Sasaki H. Nanjo K. Diabetes. 2004; 53: 482-485Crossref PubMed Scopus (92) Google Scholar). Individuals with the –866 A/A genotype also have enhanced UCP2 transcriptional activity and elevated UCP2 expression (10Sesti G. Cardellini M. Marini M.A. Frontoni S. D'Adamo M. Del Guerra S. Lauro D. De Nicolais P. Sbraccia P. Del Prato S. Gambardella S. Federici M. Marchetti P. Lauro R. Diabetes. 2003; 52: 1280-1283Crossref PubMed Scopus (123) Google Scholar). Human islets isolated from –866 A/A donors have lower GSIS than those isolated from –866 G/A heterozygous and G/G homozygous individuals (10Sesti G. Cardellini M. Marini M.A. Frontoni S. D'Adamo M. Del Guerra S. Lauro D. De Nicolais P. Sbraccia P. Del Prato S. Gambardella S. Federici M. Marchetti P. Lauro R. Diabetes. 2003; 52: 1280-1283Crossref PubMed Scopus (123) Google Scholar). In addition, increased UCP2 expression in individuals with the homozygous –866 A allele is associated with a reduction in oxidative stress and coronary heart disease (11Dhamrait S.S. Stephens J.W. Cooper J.A. Acharya J. Mani A.R. Moore K. Miller G.J. Humphries S.E. Hurel S.J. Montgomery H.E. Eur. Heart J. 2004; 25: 468-475Crossref PubMed Scopus (94) Google Scholar). These human studies suggest that the variation seen in insulin secretion from individual to individual may be in part due to the –866 G/A UCP2 promoter polymorphism and that increased UCP2 can attenuate GSIS by altering substrate oxidation. Induction of pancreatic β-cell UCP2 in vivo and in vitro has a negative impact on GSIS, likely by limiting increases in ATP production following dissipation of the proton gradient generated by glucose metabolism (12Hong Y. Fink B.D. Dillon J.S. Sivitz W.I. Endocrinology. 2001; 142: 249-256Crossref PubMed Scopus (108) Google Scholar, 13Joseph J.W. Koshkin V. Zhang C.Y. Wang J. Lowell B.B. Chan C.B. Wheeler M.B. Diabetes. 2002; 51: 3211-3219Crossref PubMed Scopus (192) Google Scholar, 14Zhang C.Y. Baffy G. Perret P. Krauss S. Peroni O. Grujic D. Hagen T. Vidal-Puig A.J. Boss O. Kim Y.B. Zheng X.X. Wheeler M.B. Shulman G.I. Chan C.B. Lowell B.B. Cell. 2001; 105: 745-755Abstract Full Text Full Text PDF PubMed Scopus (825) Google Scholar). What regulates UCP2 and the physiological role of this protein in the pancreatic β-cell are not well understood. It is known that free fatty acids (FFA) and reactive oxygen species (ROS) increase the expression and activity of UCP2 (5Echtay K.S. Roussel D. St Pierre J. Jekabsons M.B. Cadenas S. Stuart J.A. Harper J.A. Roebuck S.J. Morrison A. Pickering S. Clapham J.C. Brand M.D. Nature. 2002; 415: 96-99Crossref PubMed Scopus (1150) Google Scholar, 15Echtay K.S. Murphy M.P. Smith R.A. Talbot D.A. Brand M.D. J. Biol. Chem. 2002; 277: 47129-47135Abstract Full Text Full Text PDF PubMed Scopus (359) Google Scholar). This is an important interaction because increased FFA metabolism leads to an increase in energy flux through the electron transport chain, which can lead to an increase in the production of ROS in β-cells (16Carlsson C. Borg L.A. Welsh N. Endo. 1999; 140: 3422-3428Crossref PubMed Google Scholar, 17Barbu A. Welsh N. Saldeen J. Mol. Cell. Endocrinol. 2002; 190: 75-82Crossref PubMed Scopus (112) Google Scholar). UCP2 may be involved in this interaction by limiting the FFA-stimulated increase in ROS production by dissipating the excess energy (15Echtay K.S. Murphy M.P. Smith R.A. Talbot D.A. Brand M.D. J. Biol. Chem. 2002; 277: 47129-47135Abstract Full Text Full Text PDF PubMed Scopus (359) Google Scholar). However, ROS-mediated activation of UCP2 is now thought to be an important determinant of impaired GSIS (18Krauss S. Zhang C.Y. Scorrano L. Dalgaard L.T. St Pierre J. Grey S.T. Lowell B.B. J. Clin. Investig. 2003; 112: 1831-1842Crossref PubMed Scopus (333) Google Scholar). We propose that UCP2 may play a protective role in the β-cell by mitigating the consequences of excess FFA- and glucose-induced ROS production. However, in protecting from ROS the increased β-cell UCP2 activity down-regulates GSIS. Previously, we used a well characterized in vivo model in which mice were treated with a high fat diet (HFD) for 4.5 months, and we found that UCP2(–/–) mice were resistant to the effects of a HFD in terms of β-cell function. To understand the cellular responses of UCP2(–/–) β-cells to FFA, we utilized a well known in vitro model of lipotoxicity in which isolated islets or dispersed β-cells were treated with control medium or medium containing 0.4 mm palmitate for 48 h (6Krauss S. Zhang C.Y. Lowell B.B. Proc. Natl. Acad. Sci. U. S. A. 2002; 99: 118-122Crossref PubMed Scopus (154) Google Scholar, 13Joseph J.W. Koshkin V. Zhang C.Y. Wang J. Lowell B.B. Chan C.B. Wheeler M.B. Diabetes. 2002; 51: 3211-3219Crossref PubMed Scopus (192) Google Scholar). We then examined a number of key metabolic parameters involved in GSIS including insulin content, FFA metabolism, mitochondrial membrane potential, ATP/ADP ratio, cytosolic Ca2+ changes, and insulin secretion. We showed that UCP2(–/–) islets had no alterations in mitochondrial membrane potential, ATP/ADP ratio, and cytosolic Ca2+ responses after palmitate treatment, whereas wild type (WT) islets showed dysfunctional responses. We also found that palmitate did not increase ROS in UCP2(–/–) β-cells. Therefore UCP2(–/–) mice maintained robust glucose-dependent metabolism-secretion coupling after FFA exposure that reverted to a WT islet phenotype after UCP2 overexpression in UCP2(–/–) islets. Reagents—Carbonyl cyanide p-(trifluoromethoxy) phenylhydrazone (FCCP), ATP sulfurylase, pyruvate kinase, collagenase type V and type XI, ATP luciferase, d-luciferin, ATP, and ADP were all purchased from Sigma. Animals—Male UCP2 (WT) or UCP2 knockout (–/–) mice at 4 months of age were used in the present study and were bred from lines generated as described previously (13Joseph J.W. Koshkin V. Zhang C.Y. Wang J. Lowell B.B. Chan C.B. Wheeler M.B. Diabetes. 2002; 51: 3211-3219Crossref PubMed Scopus (192) Google Scholar, 14Zhang C.Y. Baffy G. Perret P. Krauss S. Peroni O. Grujic D. Hagen T. Vidal-Puig A.J. Boss O. Kim Y.B. Zheng X.X. Wheeler M.B. Shulman G.I. Chan C.B. Lowell B.B. Cell. 2001; 105: 745-755Abstract Full Text Full Text PDF PubMed Scopus (825) Google Scholar). For the HFD studies, half of the mice were placed on either a control diet (rodent diet 8664, Harlan Teklad, Madison, WI) or a HFD (D12451, Research Diets Inc., New Brunswick, NJ). The fat source was lard, comprising 45% of the total calories. The mice remained on the HFD or control diet for 4.5 months (13Joseph J.W. Koshkin V. Zhang C.Y. Wang J. Lowell B.B. Chan C.B. Wheeler M.B. Diabetes. 2002; 51: 3211-3219Crossref PubMed Scopus (192) Google Scholar). Intraperitoneal glucose tolerance tests were performed as described previously (14Zhang C.Y. Baffy G. Perret P. Krauss S. Peroni O. Grujic D. Hagen T. Vidal-Puig A.J. Boss O. Kim Y.B. Zheng X.X. Wheeler M.B. Shulman G.I. Chan C.B. Lowell B.B. Cell. 2001; 105: 745-755Abstract Full Text Full Text PDF PubMed Scopus (825) Google Scholar). Plasma insulin levels were determined using a rat insulin enzyme-linked immunosorbent assay kit (Crystal Chem, Chicago, IL). Adenoviral Vectors—Adenoviral vectors used in these studies are described elsewhere and include adenovirus expressing UCP2 (AdUCP2) (12Hong Y. Fink B.D. Dillon J.S. Sivitz W.I. Endocrinology. 2001; 142: 249-256Crossref PubMed Scopus (108) Google Scholar), adenovirus expressing enhanced yellow fluorescent protein driven by the rat insulin promoter-2 (AdRIP2EYFP) (19Kang G.X. Joseph J.W. Chepurny O.G. Monaco M. Wheeler M.B. Bos J.L. Schwede F. Genieser H.G. Holz G.G. J. Biol. Chem. 2003; 278: 8279-8285Abstract Full Text Full Text PDF PubMed Scopus (257) Google Scholar), and adenovirus expressing enhanced green fluorescent protein driven by a cytomegalovirus promoter (AdEGFP) (7Chan C.B. MacDonald P.E. Saleh M.C. Johns D.C. Marban E. Wheeler M.B. Diabetes. 1999; 48: 1482-1486Crossref PubMed Scopus (229) Google Scholar). Adenovirus-mediated overexpression of enhanced green fluorescent protein (EGFP) was used as a control for the overexpression of UCP2 using AdUCP2. Real-time PCR Analysis of UCP2 mRNA Expression—UCP2 mRNA levels were detected by real-time PCR as described (13Joseph J.W. Koshkin V. Zhang C.Y. Wang J. Lowell B.B. Chan C.B. Wheeler M.B. Diabetes. 2002; 51: 3211-3219Crossref PubMed Scopus (192) Google Scholar). Briefly, UCP2- and GAPDH-specific fluorescent probes were obtained from Biosearch Technologies Inc. (Novato, CA) (13Joseph J.W. Koshkin V. Zhang C.Y. Wang J. Lowell B.B. Chan C.B. Wheeler M.B. Diabetes. 2002; 51: 3211-3219Crossref PubMed Scopus (192) Google Scholar). UCP2 and GAPDH expression levels were measured simultaneously using a Taqman Universal PCR master mix and an ABI Prism 7900HT sequence detection system (Applied Biosystems, Branchburg, NJ). All mRNA levels were quantified using a standard curve of a known amount of mouse cDNA (cDNAs were created from forward and reverse primers (13Joseph J.W. Koshkin V. Zhang C.Y. Wang J. Lowell B.B. Chan C.B. Wheeler M.B. Diabetes. 2002; 51: 3211-3219Crossref PubMed Scopus (192) Google Scholar)). All cDNA PCR products that were used in the standard curve were purified using a MinElute PCR purification kit (Qiagen, Mississauga, Ontario, Canada). The real-time PCR conditions were 2 min at 50 °C, 10 min at 95 °C, and then 40 cycles for 15 s at 95 °C and 1 min at 53 °C. UCP2 mRNA levels were corrected for GAPDH levels by dividing UCP2 mRNA levels by GAPDH mRNA levels. There were no differences in GADPH levels between treatments. Western Blot Analysis of UCP2 Protein Expression—Ambient and virally induced expression of UCP2 was assessed by immunoblotting. UCP2 was detected using goat anti-UCP2 antibody (Research Diagnostic Inc., 1:400), and the secondary antibody was peroxidase-conjugated donkey anti-goat (Jackson Immunoresearch, 1:5000). Pancreatic Islet Isolation—Pancreatic islets were isolated as described previously (13Joseph J.W. Koshkin V. Zhang C.Y. Wang J. Lowell B.B. Chan C.B. Wheeler M.B. Diabetes. 2002; 51: 3211-3219Crossref PubMed Scopus (192) Google Scholar, 14Zhang C.Y. Baffy G. Perret P. Krauss S. Peroni O. Grujic D. Hagen T. Vidal-Puig A.J. Boss O. Kim Y.B. Zheng X.X. Wheeler M.B. Shulman G.I. Chan C.B. Lowell B.B. Cell. 2001; 105: 745-755Abstract Full Text Full Text PDF PubMed Scopus (825) Google Scholar, 20Lacy P.E. Kostianovsky M. Diabetes. 1967; 16: 35-39Crossref PubMed Scopus (2492) Google Scholar). Briefly, the pancreatic duct was perfused with 3 ml of collagenase (3 mg/ml). The pancreas was then chopped into 2-mm pieces and digested by shaking (50 rpm) for 10–15 min at 37 °C. Islets were partially isolated by sedimentation and then hand picked from the acinar tissue debris. Islet Dispersion—Freshly isolated islets were incubated for 8–9 min at room temperature in Krebs-Ringer-bicarbonate-HEPES (KRBH) buffer with 1 mm EDTA, 0.2% (w/v) bovine serum albumin, and 5.6 mm glucose. KRBH buffer contained (in mm) 118 NaCl, 4.4 KCl, 1.2 MgCl2, 1.5 KH2PO4, 5 NaHCO3, and 10 HEPES, pH 7.4. Islets were further incubated in KRBH buffer containing 1 mm EDTA, trypsin (25 μg/ml, Sigma), and DNase I (2 μg/ml, Sigma) at 37 °C for 9 min with gentle pipetting every 2 min. The cells were washed twice in the islet culture medium RPMI (Roswell Park Memorial Institute) supplemented with 5.6 mm glucose, 0.25% HEPES (Sigma), 20 units/ml penicillin G sodium, and 20 μg/ml streptomycin sulfate (Invitrogen). Cells were then plated onto collagen-coated glass cover slips and allowed to attach overnight in islet culture medium containing 10% fetal bovine serum (Invitrogen). Islet and Dispersed β-Cell Culture—Islets and dispersed β-cells were preincubated for 24 h in islet culture medium containing 10% (v/v) fetal bovine serum and then transferred to control medium (culture medium with 5% (v/v) fetal bovine serum and 0.25% (w/v) bovine serum albumin without free fatty acids (Sigma)) or palmitate medium (control medium with 0.4 mm palmitate) for 48 h. In some experiments using UCP2(–/–) islets or dispersed β-cells, UCP2 was reintroduced using AdUCP2 at the beginning of the 48-h culture period at a multiplicity of infection of 5 × 103. Islet Triglyceride Measurements—Triglycerides (TG) were extracted from groups of 100 islets by lipid extraction in a chloroform/methanol (2:1 v/v) mixture as described elsewhere (21Folch J. Lees M. Sloane-Stanley G.H. J. Biol. Chem. 1957; 226: 497-509Abstract Full Text PDF PubMed Google Scholar, 22Briaud I. Harmon J.S. Kelpe C.L. Segu V.B. Poitout V. Diabetes. 2001; 50: 315-321Crossref PubMed Scopus (254) Google Scholar). For the assay, the dry material derived from evaporation of the chloroform phase was resuspended in water in the presence of a detergent (Thesit or polidocanol (Sigma) 20% w/v in chloroform). TGs were measured enzymatically with a commercial kit (GPO Trinder; Sigma). Triolein (Sigma), which was dissolved in chloroform/methanol and processed similarly to samples, was used as the standard. Islet β-Oxidation—Palmitate oxidation in isolated islets was measured as described previously (23Chen S.Y. Ogawa A. Ohneda M. Unger R.H. Foster D.W. McGarry J.D. Diabetes. 1994; 43: 878-883Crossref PubMed Scopus (167) Google Scholar). In brief, 50 islets per condition were incubated in KRBH experimental medium containing 2.8 or 22 mm glucose, 1% fatty acid-free bovine serum albumin, 0.8 mm carnitine, and 1 μCi of [14C]palmitate (Amersham Biosciences) for 2 h at 37 °C in an orbital water bath (100 cycles/min). The reaction was stopped by the addition of perchloric acid, and the evolved 14CO2 was captured with hyamine hydroxide with shaking for an additional 2 h. Mitochondrial Membrane Potential Imaging—Glucose-induced changes in mitochondrial membrane potential (Δψm) were quantified in dispersed β-cells. After the 48-h treatment period, cells were loaded with rhodamine 123 (2.6 μm Rh123 for 15 min) (Molecular Probes, Eugene, OR). Fluorescence was excited at 490 nm and measured at 530 nm. All membrane potential measurements were done at 37 °C. Images were captured and analyzed using the Merlin software (Olympus America, Life Sciences Resources, Melville, NY) as described elsewhere (13Joseph J.W. Koshkin V. Zhang C.Y. Wang J. Lowell B.B. Chan C.B. Wheeler M.B. Diabetes. 2002; 51: 3211-3219Crossref PubMed Scopus (192) Google Scholar, 24Smukler S.R. Tang L. Wheeler M.B. Salapatek A.M. Diabetes. 2002; 51: 3450-3460Crossref PubMed Scopus (91) Google Scholar). Exposure time was 0.2 s, and images were acquired at ∼0.2 Hz. Rh123 is a fluorescent lipophilic cationic dye that specifically partitions into negatively charged mitochondrial membranes. Under these Rh123 loading conditions, hyperpolarization of the Δψm as seen after nutrient stimulation results in an increase in the Rh123 concentration in the mitochondrial membrane, leading to an aggregation of dye molecules and quenching of the fluorescence signal. Conversely, depolarization of Δψm allows the dye to redistribute from the mitochondria into the cytosol, resulting in an increase of the Rh123 signal (25Drucker D.J. Campos R. Reynolds R. Stobie K. Brubaker P.L. Endocrinology. 1991; 128: 394-400Crossref PubMed Scopus (50) Google Scholar). Changes in fluorescence from 2.8 to 20 mm glucose were determined by comparison with the average base-line fluorescence over the first 50 s, which was arbitrarily assigned a value of 1.0. Assessment of the glucose-induced changes was done by averaging data between 500–700 s and comparing the normalized values to the base line. At the end of an experiment 1 μm FCCP was added to assess cell viability and to test the ability of the cell loaded with Rh123 to respond to changes in the Δψm induced by the chemical uncoupler. Islet GSIS, ADP, and ATP Determination—Groups of 25 islets were preincubated in experimental medium for two sequential 30-min periods at 37 °C, 5% CO2. Islets were then incubated for 2 h at the indicated glucose concentration (either 2.8 or 16.7 mm glucose) to assess insulin secretion. Islet DNA and insulin secretion measurements were performed as described previously (13Joseph J.W. Koshkin V. Zhang C.Y. Wang J. Lowell B.B. Chan C.B. Wheeler M.B. Diabetes. 2002; 51: 3211-3219Crossref PubMed Scopus (192) Google Scholar). Islet ATP and ADP content was determined using these same islets at the end of the 2-h incubation period using the method of Tornheim and co-workers (26Schultz V. Sussman I. Bokvist K. Tornheim K. Anal. Biochem. 1993; 215: 302-304Crossref PubMed Scopus (56) Google Scholar). In brief, islet ATP and ADP were extracted from the 25 islets with 20 units of 10% (w/v) perchloric acid. After centrifugation, the supernatants were neutralized with 2 n KOH, 0.5 m triethanolamine and then freeze-dried (SpeedVac). Aliquots of each deproteinized sample were assayed for ATP directly with luciferase (Sigma). Other aliquots were treated with ATP sulfurylase in the presence of molybdate to hydrolyze the endogenous ATP to AMP and PPi. After boiling the samples to inactivate the sulfurylase, ADP was then converted to ATP with pyruvate kinase and phosphoenolpyruvate for measurement with luciferase. Islet Insulin Content Measurements—At the end of a GSIS experiment and after extracting ATP and ADP, insulin was solubilized from the perchloric acid protein pellet by adding 0.5 n NaOH and heating to 60 °C for 10 min and then neutralized with 2 n HCl. Insulin secretion and insulin content were determined as described previously (27Brubaker P.L. Lee Y.C. Drucker D.J. J. Biol. Chem. 1992; 267: 20728-20733Abstract Full Text PDF PubMed Google Scholar, 28Brubaker P.L. So D.C.Y. Drucker D.J. Endocrinology. 1989; 124: 3003-3009Crossref PubMed Scopus (31) Google Scholar). Ca2+Imaging—Ca2+ imaging was performed on dispersed β-cells plated on collagen-coated cover slips. Data collection was performed with the same equipment used for Rh123 imaging. After dispersion, cells were infected with AdRIP2EYFP and then cultured with either control or palmitate medium for 48 h. Cells were then loaded with 1 μm Fura-2/AM (Molecular Probes) for 45 min at 37 °C. β-Cells were identified using the fluorescence of the EYFP driven by the rat insulin promoter (excitation 490 nm, emission 530 nm). Experiments were performed at 37 °C. Images were obtained with 340- and 380-nm excitation and a 510-nm cutoff emission filter. Exposures lasted 0.2 s, and images were acquired at ∼0.2 Hz. Images were collected and analyzed using the Merlin software (13Joseph J.W. Koshkin V. Zhang C.Y. Wang J. Lowell B.B. Chan C.B. Wheeler M.B. Diabetes. 2002; 51: 3211-3219Crossref PubMed Scopus (192) Google Scholar). Data were averaged, and the standard error of the mean was plotted for data points every 40 s. Reactive Oxygen Species—ROS were detected in islets using 2′,7′-dichlorodihydrofluorescein diacetate (DCF) (Sigma). Islets were loaded with 10 μm dye in KRBH buffer (containing 5.6 mm glucose) for 20 min at room temperature. Fluorescence of oxidized dye, reflecting cellular oxidation status, was measured with the equipment used for rhodamine 123 imaging (excitation/emission wavelengths 495/530 nm) in KRBH buffer in the presence of 5.6 mm glucose. Images were collected in 30-s intervals with 150-ms exposures and minimal intensity of exciting light. Islet ROS was quantified using standard curves obtained with solutions of the oxidized probe DCF. Statistics—Statistical significance was assessed by using either Student's t test or one-way or two-way analysis of variance for repeated measures followed by multiple Bonferroni comparisons. All data are expressed as means ± S.E. Islet Triglyceride, β-Oxidation, and Insulin Content—Increased islet TG are associated with an inhibition of GSIS. To ascertain the effects of a HFD on islet TG levels in vivo, mice were fed a HFD for 4.5 months (13Joseph J.W. Koshkin V. Zhang C.Y. Wang J. Lowell B.B. Chan C.B. Wheeler M.B. Diabetes. 2002; 51: 3211-3219Crossref PubMed Scopus (192) Google Scholar). To confirm our previous results, where enhanced insulin secretion in UCP2(–/–) mice was observed after a HFD, an intraperitoneal glucose tolerance test was performed. Both basal and glucose-stimulated (10 min after intraperitoneal injection of glucose) insulin levels were significantly higher in UCP2(–/–) mice on the control or the HFD (Fig. 1A). There was no difference in islet TG concentrations between islets from WT and UCP2(–/–) mice on the control diet (Fig. 1B). After HFD treatment, WT islets had increased TG content compared with UCP2(–/–) islets (Fig. 1B). No detectable UCP2 mRNA or protein levels could be identified in UCP2(–/–) mouse islets infected with either no virus or a control adenovirus (AdEGFP) or when treated with 0.4 mm palmitate (data not shown). Culture of WT islets in 0.4 mm palmitate for 48 h increased UCP2 mRNA expression levels 8-fold over WT control medium-treated islets (UCP2/GAPDH ratio of 0.0372 ± 0.0013 versus 0.0047 ± 0.0001, respectively). UCP2 protein levels were also increased in palmitate-treated WT islets (Fig. 2A). In UCP2(–/–) islets, AdUCP2 increased UCP2 mRNA expression levels 435-fold over WT control medium-treated islets (UCP2/GAPDH ratio of 2.030 ± 0.2891 versus 0.0047 ± 0.0001, respectively). AdUCP2 increased UCP2 protein levels in UCP2(–/–) islets as determined by Western blotting (Fig. 2A). In the in vitro study in which islets were exposed to 0.4 mm palmitate for 48 h, islet TG content was not different between the groups of islets (WT, UCP2(–/–), and UCP2(–/–) overexpressing UCP2) treated with control medium (Fig. 2B). There was a significa